Genome-wide survey of efflux pump-coding genes associated with Cronobacter survival, osmotic adaptation, and persistence. (December 2019) - Negrete, Flavia; Jang, Hyein; Gangiredla, Jayanthi; Woo, JungHa; Lee, YouYoung; Patel, Isha R; Chase, Hannah R; Finkelstein, Samantha; Wang, Caroline Z; Srikumar, Shabarinath; Nguyen, Scott; Eshwar, Athmanya; et al.
Highlights: Cronobacter species possess species-specific efflux pump orthologues. For C. sakazakii, the acquisition of efflux pumps genes followed sequence type phylogeny. Efflux pump genes were acquired through microevolution and/or horizontal gene transfer. Efflux activity is important in osmotic adaptation, survival, and persistence of Cronobacter species. Abstract : Microorganisms express various transmembrane complexes collectively known as efflux pumps that influence their survival under stressful growth conditions. Although efflux pumps are important in resistance to antibiotics, disinfectants, and preservatives, little information about their presence and roles in Cronobacter spp. is available. To better understand the phylogeny, prevalence, and distribution of efflux pumps among strains of Cronobacter spp., whole genome sequencing (WGS) and pan-genomic DNA microarray (MA) analysis were carried out. Targeted MA analysis with 156 probe set alleles representing efflux pump genetic loci showed that all seven Cronobacter species possessed species-specific efflux pump orthologues. Distribution of the efflux pump genes and sequence variations were studied using WGS datasets. Phylogenetic and molecular clock analyses showed that the acquisition of these efflux pump genes possibly occurred at separate evolutionary events, which most likely correlated with the evolution of sequence type (ST) lineages. The acquisition of efflux pump genes either occurred as independent evolutionary events through horizontal gene transfer, or in certain situations, such as that for ST83 and ST4 strains, they could have been acquired through a robust microevolutionary selective process, some of which may have provided functional advantages. Efflux pump activity is very important in osmotic adaptation, survival, and persistence of Cronobacter species and are involved in several important physiological processes including protein, heavy metal, and sugar efflux. Understanding the mechanisms of Cronobacter adaptation in a wide range of environments, could eventually lead to development of methods to control the contamination of foods by these organisms.